Early experience with robotic navigation for catheter ablation of paroxysmal atrial fibrillation - Kautzner, Josef; Peichl, Petr; Cihák, Robert; Wichterle, Dan; Mlcochová, Hanka (Pacing and clinical electrophysiology, 2009)
INTRODUCTION: Pulmonary venous antra isolation (PVAI) is the cornerstone of catheter ablation procedure for drug refractory paroxysmal atrial fibrillation (AF). However, the procedure is technically challenging. Robotic navigation has a potential to expedite and facilitate the procedure. METHODS: A robotic catheter control system was used for remote navigation-supported PVAI in 22 patients (mean age = 55 +/- 9 years, 16 males, study group). An irrigated-tip catheter with estimate of catheter force on the tissue was used. This was compared in nonrandomized fashion with conventional hand-controlled catheter ablation in 16 patients (mean age = 55 +/- 9 years, 13 males, control group). The procedures were performed under guidance of Ensite NavX navigation system (St. Jude Medical, St. Paul, MN, USA) and intracardiac echocardiography. RESULTS: Robotic navigation was associated with significantly shorter overall duration of radiofrequency delivery (1,641 +/- 609 vs 2,188 +/- 865 seconds, P < 0.01), shorter total procedural time (207 +/- 29 vs 250 +/- 62 minutes, P = 0.007), fluoroscopy exposure (15 +/- 5 vs 27 +/- 9 minutes, P < 0.001), and lower radiation dose (1,119 +/- 596 vs 3,048 +/- 2,029 mGy/m(2), P < 0.001). No complication was observed in either the study or the control group. During the 5 +/- 1 months follow-up in the study group and 9 +/- 3 months in the control group, 91% and 81% of patients, respectively, were AF free. CONCLUSIONS: In our early clinical experience, PVAI using a remote robotic catheter navigation was effective, safe, and associated with shorter procedural and fluoroscopic times than conventional PVAI.
Keywords: Pulmonary Veins; chirurgie s pomocí počítače; Robotics; výsledek terapie; katetrizační ablace; mapování potenciálů tělesného povrchu; Middle Aged; mužské pohlaví; Body Surface Potential Mapping; Catheter Ablation; ženské pohlaví; Humans; venae pulmonales; fibrilace síní; pilotní projekty; lidé středního věku; Pilot Projects; Female; Surgery, Computer-Assisted; Atrial Fibrillation; robotika; Treatment Outcome; lidé; Male